Stres psikososial kronis dengan kejadian hipertensi pada pekerja lapangan pabrik gula PT. Indolampung Perkasa - Rahma Elliya; Marliyana Marliyana; Yulianto Yulianto (Holistik Jurnal Kesehatan, 2020)
Chronic psychosocial stress and hypertension among sugar cane plantation workers in Lampung, IndonesiaBackground: The background of this research is based on data obtained from the 2016 Tulang Bawang District Health Office; hypertension is one of the causes of death. In 2016 the number of deaths from hypertension in Tulang Bawang Regency was 34 cases. Based on the results of the pre-survey by researchers, it was known from 532 workers who went to the Medical Clinic at PT. Indolampung Perkasa diagnosed with hypertension as many as 168 (31.57%) people.Purpose: Knowing correlation between chronic psychosocial stress and hypertension among sugar cane plantation workers in Lampung Indonesia.Methods: Type of study was quantitative, with cross sectional design. The populations of this study were all sugar cane plantation workers at PT. Indolampung Perkasa and sample of 229 respondents. Data collection was primary, directly to respondents by distributing questionnaires. Data analysis was chi square with OR 2.637.Results: It was known from 229 respondents with hypertension, as many as 79 (34.5%) respondents were hypertensive and as many as 150 (65.5%) respondents were not hypertensive. Known from 229 respondents with stress, as many as 82 (35.8%) respondents were stressed and as many as 147 (64.2%) respondents were not stressed with (p-value 0.001; OR 2,637).Conclusion: There were correlation between chronic psychosocial stress and hypertension among sugar cane plantation workers in Lampung Indonesia.Keywords: Chronic psychosocial stress; Hypertension; Sugar cane plantation workersPendahuluan: Berdasarkan data yang diperoleh dari Dinas Kesehatan Kabupaten Tulang Bawang tahun 2016, penyakit hipertensi menjadi salah satu penyebab kematian. Pada tahun 2016 jumlah kematian akibat hipertensi di Kabupaten Tulang Bawang sebanyak 34 kasus. Berdasarkan hasil pra survey yang dilakukan peneliti diketahui dari 532 orang pekerja yang berobat ke Medical Clinic PT. Indolampung Perkasa dengan diagnosa hipertensi sebanyak 168 (31,57%) orang.Tujuan: Diketahui hubungan stres psikososial kronis dengan kejadian hipertensi pada pekerja lapangan.Metode: Jenis penelitian kuantitatif, dengan desain / rancangan cross sectional. Populasi sebanyak 532, sampel sebanyak 229 responden. Pengumpulan data secara primer, langsung kepada responden dengan membagikan kuesioner. Analisis data secara univariat (distribusi frekuensi) dan bivariat (chi square) dengan nilai OR 2,637.Hasil: Diketahui dari 229 responden dengan hipertensi, sebanyak 79 (34,5%) responden yang hipertensi dan sebanyak 150 (65,5%) responden yang tidak hipertensi. Diketahui dari 229 responden dengan stres psikososial kronis, sebanyak 82 (35,8%) responden yang stres psikososial kronis dan sebanyak 147 (64,2%) responden yang tidak stres psikososial kronis dengan (p-value 0,001 ; OR 2,637).Simpulan: Ada hubungan stres psikososial kronis dengan kejadian hipertensi pada pekerja lapangan.